2011
DOI: 10.1029/2010jd015431
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface emission effects in AMSR-E measurements: Implications for land surface microwave emissivity retrieval

Abstract: [1] An analysis of land surface microwave emission time series shows that the characteristic diurnal signatures associated with subsurface emission in sandy deserts carry over to arid and semiarid regions worldwide. Prior work found that diurnal variation of Special Sensor Microwave/Imager (SSM/I) brightness temperatures in deserts was small relative to International Satellite Cloud Climatology Project land surface temperature (LST) variation and that the difference varied with surface type and was largest in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…Although the assumptions inherent in these formulations are major simplifications of the actual properties of terrestrial surfaces, this construct has been shown to be a useful first‐order quantification of penetration effects, wherein α ν represents spatial and temporal variations in penetration. The assumptions are tested in the quality control process using the model fit error [ Galantowicz et al , 2011].…”
Section: Emissivity Retrieval Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the assumptions inherent in these formulations are major simplifications of the actual properties of terrestrial surfaces, this construct has been shown to be a useful first‐order quantification of penetration effects, wherein α ν represents spatial and temporal variations in penetration. The assumptions are tested in the quality control process using the model fit error [ Galantowicz et al , 2011].…”
Section: Emissivity Retrieval Methodologymentioning
confidence: 99%
“…Wherever the criteria for creating class‐based emissivities (section 3.4) are met, they override the default. The PTS products are used for all grid points that pass a series of tests for reliability of the PTS retrieval and significance of microwave penetration, considering data sample sizes and measures of the quality of the fit between the data and the penetration model [ Galantowicz et al , 2011]. By these criteria, the PTS products are selected for a substantial portion of the global land, responding to arid conditions well beyond deserts.…”
Section: Merged Productsmentioning
confidence: 99%
“…In addition to factors highlighted in this study, many other ones, such as instrument errors (e.g., [18]), calibration errors, differences in locations and resolutions of the satellite footprints, spatial and temporal sampling errors, and representativeness of surface properties over highly heterogeneous and dynamic surfaces (e.g., desert) [13], [19], [20], all contribute to the complexity of the retrieval process and the associated errors. It is therefore necessary to recognize the limitations in these instantaneous retrievals, and to develop strategies to alleviate their impact while exacting as much useful information as possible.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…We speculate this might be related to the strong diurnal cycle in the variation of the surface temperature and the microwave penetration depth, which makes it tricky to represent the effective emission characteristics in the retrieval process [13], [17], [19], [20].…”
Section: B Histograms Of Emissivity Retrievalsmentioning
confidence: 99%
“…Second, temperature retrieval from PMW measurements yields subsurface temperature, which is different from LST retrieval from TIR measurements (skin temperature). Nevertheless, subsurface temperatures can be converted to skin temperatures using the thermal diffusion equation (Gao et al, 2010;Moncet et al, 2011;Galantowicz et al, 2011). Third, the accuracies (approximately 5-6 K) of subsurface temperature retrieval from PMW measurements are worse than those (approximately 1-2 K) of LST retrieval from TIR measurements.…”
Section: Introductionmentioning
confidence: 99%